Jorge de Sena y Dionisio Ridruejo: 11 cartas y algunos versos - Vieira, Inês Espada (2021)
The poets Jorge de Sena (1919-1978) and Dionisio Ridruejo (1912-1975) met as professors at the University of Wisconsin-Madison in 1968 and began a friendship that would last until the end of their lives, sharing the literary and cultural life of their home countries with other Portuguese and Spanish writers and intellectuals. This work presents the unpublished correspondence between Sena and Ridruejo, establishing a relationship with other evidence of their mutual coexistence and admiration, which is closely tied to the common destiny of the two Iberian countries.